An Empirical Evaluation of ADHD Coaching in College Students. (August 2015) - Prevatt, Frances; Yelland, Sherry
Objective: This study evaluated a program for ADHD coaching in a sample of college students.Method: ADHD coaching was conducted with 148 college students over a 5-year period. The theoretical orientation combined cognitive-behavioral therapy with psychoeducational techniques. Executive functioning served as a way of viewing both initial problem areas and outcomes.Results: Clients who received an 8-week coaching program showed significant improvement in all 10 areas of study and learning strategies, on self-esteem, and on measures of symptom distress and satisfaction with school and work. These results were consistent across different semesters and time of semester, and with a variety of different coaches, all of whom were novice coaches.Conclusion: This study provides important preliminary information about ADHD coaching, including coaching structure, processes, efficacy, and correlates of positive outcomes. Additional evaluations utilizing a randomized controlled design are needed.